Potentially pathogenic free-living amoebae in some flood-affected areas during 2011 Chiang Mai flood - Anchalee Wannasan (2018)
The survey was carried out to investigate the presence of potentially pathogenic free-living amoebae (FLA) during flood in Chiang Mai, Thailand in 2011. From different crisis flood areas, seven water samples were collected and tested for the presence of amoebae using culture and molecular methods. By monoxenic culture, FLA were detected from all samples at 37 °C incubation. The FLA growing at 37 °C were morphologically identified as Acanthamoeba spp., Naegleria spp. and some unidentified amoebae. Only three samples (42.8%), defined as thermotolerant FLA, continued to grow at 42 °C. By molecular methods, two non-thermotolerant FlA were shown to have 99% identity to Acanthamoeba sp. and 98% identity to Hartmannella vermiformis while the two thermotolerant FLA were identified as Echinamoeba exundans (100% identity) and Hartmannella sp. (99% identity). This first report of the occurrence of FLA in water during the flood disaster will provide information to the public to be aware of potentially pathogenic FLA.